Molecular and cellular mechanisms leading to catatonia: an integrative approach from clinical and preclinical evidence - Ariza-Salamanca, Daniel Felipe; Corrales-Hernández, María Gabriela; Pachón-Londoño, María José; Hernández-Duarte, Isabella (Frontiers in Molecular Neuroscience, 2022)
This review aims to describe the clinical spectrum of catatonia, in order to carefully assess the involvement of astrocytes, neurons, oligodendrocytes and microglia, and articulate the available preclinical and clinical evidence to achieve a translational understanding of the cellular and molecular mechanisms behind this disorder. Catatonia is highly common in psychiatric and acutely ill patients, with prevalence ranging from 7.6% to 38%. It is usually present in different psychiatric conditions such as mood and psychotic disorders; it is also a consequence of folate deficiency, autoimmunity, paraneoplastic disorders, and even autistic spectrum disorders. Few therapeutic options are available due to its complexity and poorly understood physiopathology. We briefly revisit the traditional treatments used in catatonia, such as antipsychotics, electroconvulsive therapy and benzodiazepines, before assessing novel therapeutics which aim to modulate molecular pathways through different mechanisms, including NMDA antagonism and its allosteric modulation, and anti-inflammatory drugs to modulate microglia reaction and mitigate oxidative stress, such as lithium, vitamin B12, and NMDAr positive allosteric modulators.